PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN MENULIS ANAK TUNARUNGU KELAS V DI SDLB-B - Dyah Kusumaningtyas, Ervina (Jurnal Pendidikan Khusus, 2017)
ABSTRACT Hearing impairment made the speech ability disturbed which caused a complex development problem one of them was little information accepted by the children so that it had impact to their writing ability. It was needed a learning which helped the children in writing by concerning the children’s characteristics. The scientific approach was learning approach which prioritized visual sense and helped to process the information obtained during learning. This research had purpose to analyze the influence of scientific approach in learning writing especially in writing concept to Science learning. This research used quantitative approach of pre experiment research kind and one group pre-test – post-test design. The subject in this research was hearing impairment children of class V numbering 8 children. The research location was in SDLB-B Karya Mulia I Surabaya. The data collection technique was test with the data analysis technique of statistic non parametric using Wilcoxon match pair test formula. The result of analysis data indicated that the usage of scientific approach significantly influenced toward learning writing to hearing impairment children of class V in SDLB-B Karya Mulia I Surabaya. Keywords: Scientific approach, learning writing